The 2-adic complexity and the 1-error 2-adic complexity of single cycle T-functions - Wei YOU; Wen-feng QI (Tongxin xuebao)
The 2-adic complexities of the coordinate sequences derived from single cycle T-functions over F 2n were investigated.Let j be an integer such that 0≤ j≤n−1.It is shown that the 2-adic complexity of the j th coordinate sequence is upper bounded by lb(22j+1).The distribution of the corresponding 2-adic number associated with the j th coordinate sequence of all single cycle T-functions was also discussed,which implies that the upper bound is attainable.Moreover,1-error 2-adic complexity was also studied.It was proved that the 1-error 2-adic complexity of the j th coordinate sequence is equal to its 2-adic complexity except for j=0.